Analysis of Adnexal Mass in Women with Previous Hysterectomy - An observational study - Sangam JHA; Anamika SINGH; Hemali SINHA (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To characterize the clinicopathological features of adnexal masses arising subsequent to hysterectomy and portion of them requiring re-operation. In addition, average time interval between hysterectomy and diagnosis of adnexal mass was ascertained along with the need of salpingectomyMaterials and Methods: This observational study was conducted on the patients who presented with adnexal mass subsequent to hysterectomy. Data regarding characteristics of lesion, clinical presentation, proportion requiring re-operation and histological nature were analyzed.Results: Over the span of 4 years, 115 women with hysterectomy presented with adnexal mass. 93% of them had index hysterectomy abdominally. Out of this 115 patients, 45 (39%) were kept on follow-up in whom mass had resolved subsequently (expectant group) and 70 (61%) required operation for the cure (re-operation group). Median time interval to diagnosis of adnexal mass was longer in re-operation group (p < 0.001). Patients in re-operation group were more symptomatic (p = 0.011), presented with larger size (p < 0.001) and more complex cyst (p = 0.0001) with higher number of septa (p = 0.007) compared to expectant group. In 74% of patients, mass arose from the ovary and accounted for 72.3% of the benign mass and 100% of malignant mass. In remaining 26%, tube was confirmed as the source of origin. Commonest histological variety was serous cystadenoma.Conclusion: Significant number of adnexal lesion disappeared during follow up. Benign ovarian mass was the predominant lesion in re-operated group. Fallopian tube also contributed prominently in 26%, thus salpingectomy with hysterectomy shall decrease the occurrence of fallopian tube pathology.